Predicting 6000m performance time in junior rowers using a 500m indoor rowing test - da Silva, L. F.; de Almeida-Neto, P. F.; Gama, D.; Miarka, B.; Aidar, F. J.; dos Santos Silva, T.; Sabido, V.; Neto, R. B.; Slimani, M.; Dantas, P. M. S.; de Araujo Tinoco Cabral, B. G. (Preprints, 2023)
The present study aimed to develop a mathematical model to estimate the performance of an indoor rowing event of 6000m through an 500 m all out test in junior athletes. We selected 141 subjects from the Brazilian rowing confederation database (15.9 ± 1.0 years), subsequently randomised the sample to the development (~70%) and cross-validation (~30%) groups of the mathematical model. Performance data for 500m and 6000m were collected (there was a 48h washout between one test and another).Subsequently, the mathematical model: Time(min) 6000m = { [( Time(s) 500-m * 6) * 2] / 60} + 1.3, was developed by arithmetic modeling using machine learning and Regression analysis, being tested by intraclass correlation coefficient (ICC), Concordance correlation coefficient (CCC), Validity (Cb ), precision (p) and bland-Altman plotting. The prediction of the result of 6000m through the mathematical model utilizando apenas o desempenho de 500m "all-out" test showed a significant reliability in development group (r2 = 0.730, ICC = 0.753; CCC = 0.895, Cb = 0.879, p: 0.957, pure error: 0.2 secounds (1.0% estimative error)); and in cross-validation group (r2 = 0.710, ICC = 0.747; CCC = 0.888, Cb = 0.875, p: 0.903, pure error: 0.3 secounds (1.4% estimative error)). When comparing the estimated results of the 6000m performance by the mathematical model with the real performance of 6000m per-formed in indoor rowing, no statistical differences were observed. In addition, the mathematical model did not present a significant proportion bias in relation to the 6000 m performance in both groups. The mathematical model for predicting 6000m performance through a 500m fast test was significant for national level junior rowing athletes.